Cultural Elements in "Sentono Genthong" Folklore of Pacitan Regency as Literary Learning in Senior High Schools - Rizqi Citania Sari; Suyitno Suyitno; Nugraheni Eko Wardani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This aimed to describe the cultural elements in SentonoGenthong folklore in Pacitan Regency as literary learning in senior high schools. This research applied a qualitative method with an ethnographic research approach that emphasizes data on citations to folklore obtained from the results and transcripts of participant interviews and data sources from SentonoGenthong folklore in Pacitan Regency. The data were collected through interviews, observation, documentation, field notes, and transcription. They were then analysed using aspects of description, analysis, and interpretation. This research used triangulation of sources, methods, and theories. This research unravelled the description of the cultural elements in the SentonoGentong folklore in Pacitan Regency, namely (1) language systems, (2) knowledge systems, and (3) religious systems.